1998
DOI: 10.1016/s1097-2765(00)80299-3
|View full text |Cite
|
Sign up to set email alerts
|

NURD, a Novel Complex with Both ATP-Dependent Chromatin-Remodeling and Histone Deacetylase Activities

Abstract: ATP-dependent chromatin-remodeling complexes are known to facilitate transcriptional activation by opening chromatin structures. We report a novel human complex, named NURD, which contains not only ATP-dependent nucleosome disruption activity, but also histone deacetylase activity, which usually associates with transcriptional repression. The deacetylation is stimulated by ATP on nucleosomal templates, suggesting that nucleosome disruption aids the deacetylase to access its substrates. One subunit of NURD was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
749
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 894 publications
(791 citation statements)
references
References 51 publications
30
749
0
3
Order By: Relevance
“…(13) MTA1 is a subunit of the nuclear remodeling and deacetylation (NuRD) complex, which is associated with chromatin remodeling and histone deacetylase activity, leading to transcriptional regulation of specific genes. (29,30) Qian et al have reported recently that the use of chromatin remodeling agents, such as histone deacetylase All data are presented as mean ± standard deviation. inhibitor NVP-LAQ824, inhibits angiogenesis and has a greater antitumor effect in combination with the vascular endothelial growth factor receptor tyrosine kinase inhibitor PTK787/ ZK222584.…”
Section: Discussionmentioning
confidence: 99%
“…(13) MTA1 is a subunit of the nuclear remodeling and deacetylation (NuRD) complex, which is associated with chromatin remodeling and histone deacetylase activity, leading to transcriptional regulation of specific genes. (29,30) Qian et al have reported recently that the use of chromatin remodeling agents, such as histone deacetylase All data are presented as mean ± standard deviation. inhibitor NVP-LAQ824, inhibits angiogenesis and has a greater antitumor effect in combination with the vascular endothelial growth factor receptor tyrosine kinase inhibitor PTK787/ ZK222584.…”
Section: Discussionmentioning
confidence: 99%
“…HDAC1 and HDAC2 are mainly found associated in the same molecular complexes with Mi2/ NURD (nucleosome remodelling and histone deacetylase), SIN3A and Co-REST, whereas HDAC3 is found in a different complex (the nuclear co-receptor (NCOR)/ silencing mediator for retinoid and thyroid hormone receptors (SMRT) complex) [126][127][128][129][130][131][132][133] . HDAC6 has been found in cytoplasmic complexes with proteins involved in the ubiquitin signalling pathway 134 .…”
Section: Box 1 | Histone Deacetylase Complexesmentioning
confidence: 99%
“…The homologues of PKL in animal cells, CHD3 remodelers, form the Mi-2/NuRD complex with other proteins to interact with chromatin and histones to regulate transcriptional events (Ramirez and Hagman, 2009;Xue et al, 1998). To elucidate the mechanisms of how PKL regulates gene expression, we generated polyclonal antibodies against PKL for ChIP-qPCR assay.…”
Section: Pkl Binds To the Multiple Regions Of Lfy And Pkl Facilitatesmentioning
confidence: 99%